2021
DOI: 10.2147/dmso.s278928
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on Medical Nutrition Therapy for Diabesity (CoMeND) in Adults: A South Asian Perspective

Abstract: Diabetes and obesity are both increasing at a fast pace and giving rise to a new epidemic called diabesity. Lifestyle interventions including diet play a major role in the treatment of diabetes, obesity and diabesity. There are many guidelines on dietary management of diabetes or obesity globally and also from South Asia. However, there are no global or South Asian guidelines on the non-pharmacological management of diabesity. South Asia differs from the rest of the world as South Asians have different phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 105 publications
(119 reference statements)
0
28
0
Order By: Relevance
“…Eighty-five subjects with morbid obesity (BMI ≥ 35 kg/m 2 ) were recruited from the multidisciplinary obesity clinic in the hospital, and they were compared to 80 subjects with obesity (BMI ≥ 25–35 kg/m 2 ) and 85 non-obese women (BMI ≤ 25 kg/m 2 ) recruited from the community. The BMI cut-off points for obesity were defined as per the Asia-Pacific guidelines by the WHO, which suggest lower thresholds for obesity to identify the higher at-risk individuals at a lower BMI [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. This study was approved by the Institutional Review Board (IRB Min no.…”
Section: Methodsmentioning
confidence: 99%
“…Eighty-five subjects with morbid obesity (BMI ≥ 35 kg/m 2 ) were recruited from the multidisciplinary obesity clinic in the hospital, and they were compared to 80 subjects with obesity (BMI ≥ 25–35 kg/m 2 ) and 85 non-obese women (BMI ≤ 25 kg/m 2 ) recruited from the community. The BMI cut-off points for obesity were defined as per the Asia-Pacific guidelines by the WHO, which suggest lower thresholds for obesity to identify the higher at-risk individuals at a lower BMI [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. This study was approved by the Institutional Review Board (IRB Min no.…”
Section: Methodsmentioning
confidence: 99%
“…South Asian countries are mostly low middle income countries and face resource and cost challenges [ 70 ]. The guidance should be appropriate for the local healthcare delivery system, which places greater reliance on clinical medicine than investigations.…”
Section: Consensus Processmentioning
confidence: 99%
“…Overnutrition results in metabolic challenges as discussed earlier and sarcopenic obesity [ 37 , 38 ]. South Asians are increasingly leading a sedentary life style, and the region is seeing an increase in lifestyle and economic growth related non-communicable diseases in middle-aged and elderly which likely to increase secondary sarcopenia burden in this region [ 67 , 68 , [70] , [71] , [72] ].…”
Section: Consensus Processmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that MNT is not the same as diabetes self-management training and also may require ethnicity-specific adjustments. [ 26 , 34 ]. The effectiveness of MNT in T2DM was demonstrated by the Diabetes Remission Clinical Trial (DiRECT), which showed that weight loss associated with lifestyle intervention caused diabetes remission in 46% of study participants after one year.…”
Section: Strategies To Achieve T2dm Remissionmentioning
confidence: 99%